The Nature and Causes of Corruption Crimes and the Importance of International Cooperation in Combating Them: An Analytical Study on the Qatari Experience - Maasfeh, Nashat Mfudi (Journal of Economic, Administrative and Legal Sciences, 2025)
The growing global interest in combating the phenomenon of corruption is driven by the negative consequences it produces. No country is immune to the risks posed by the spread of this phenomenon, which is not confined to a particular people or nation. However, the extent and degree of corruption vary from one country to another, often depending on the environment that enables its proliferation. In countries that fail to acknowledge its existence and demonstrate no cooperation in addressing it, corruption tends to penetrate more deeply, turning such nations into attractive havens for corrupt individuals and transnational organized crime groups. These groups exploit systemic corruption to expand various illicit activities, including drug trafficking, human trafficking, money laundering, currency counterfeiting, and the illegal arms trade. Conversely, in more advanced nations where corruption cases are rare, national efforts are integrated with international initiatives to combat corruption. These countries have come to realize the profound negative impacts of corruption on political, economic, social, and security development. This research aims to clarify the concept of corruption, its main forms, causes, and effects, while highlighting the importance of international cooperation in addressing it. The study also reviews some of the key efforts undertaken by the State of Qatar in combating this phenomenon. The researcher adopted a descriptive-analytical methodology in preparing the study, which led to several key findings, most notably: 1- Legislation alone is insufficient to combat corruption without a clear and publicly declared political will that upholds transparency, accountability, and the principle of the rule of law, applied equally to all without exception.2-There is a direct correlation between the levels of corruption and the weakness of oversight and judicial institutions, making the strengthening of these institutions' independence a fundamental condition for the success of anti-corruption efforts.
Keywords: Corruption; Administrative Corruption; International Cooperation; Transparency International